Factor Structure of Students’ Psycho-Emotional Health - Kichuk, Antonina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article highlights the results of the study of health as a subject of research within the psychological scientific fields. The scientific status of the concept of «psycho-emotional health of the individual» is substantiated; its structural and component composition is presented in the staging plan. The context of the constructs «mental health», «psychological health», «emotional health» in the expansion of scientific ideas about the psycho-emotional health of students is proved.Based on the results of factor analysis, it is established that the basis of psycho-emotional health of the individual in early adulthood is the severity and significance of emotional experiences, features of the psycho-emotional sphere of personality, emotional maturity, emotional awareness, and emotional saturation of life.As a result of using factor analysis as a means of determining correlations, a four-factor model has been established, which is aimed at determining the basics of students’ psycho-emotional health. It has been empirically established that the first factor (based on expressiveness, self-regulation, empathy and integrative level of emotional maturity, emotional awareness, and integrative level of emotional intelligence) is the most loaded.The second factor was formed by indicators of psychological resourcefulness of the individual. These are such indicators as: «success», «self-confidence», «love», «creativity» and others. At the negative pole is «maladaptation». Regarding the third factor, which is conditionally called «means of self-regulation», it was formed, in particular, indicators of the following content: «work on yourself», «control», «risk-taking», as well as the parameters of meaningful life orientations. The negative poles of this factor were «consolidation» and «escanism». The fourth factor is the factor of «social conditioning». It is formed by a number of indicators: «helping others», «satisfaction with the learning process, relationships with classmates and learning activities» and others. At the negative pole of this factor is «emotional discomfort».As a result of the factor analysis, it seemed possible to establish the vectors that form the plane of the foundations of students’ psycho-emotional health. The results of multiple regression analysis contributed to the certainty in the research position on the development of psychological strategy, which takes into account the most important segments, the set of which represents the basics of psycho-emotional health of higher education, and which can be considered its predictors. Thus, determining the stages of the psychological experiment (orientation-motivational, executive, reflective-evaluative), it seemed possible to specify the current tasks and direct the psychological support of their solution.
Keywords: mental health; psychological health; emotional health; psycho-emotional health of students; meaningful life orientations of personality